Prophetic Leadership in Forming the Religious Moderation Values in Islamic Education Institutions - Arif, Moh (Cendekia: Jurnal Kependidikan dan Kemasyarakatan, 2021)
This article depicts the prophetic leadership in instilling the values of moderation in Islamic educational institutions. The enactment of prophetic leadership at Tebuireng and Mambaul Ma’arif Islamic boarding schools in Denanyar reflect various understandings and daily activities. It entails a formal situation as seen in educational institutions and non-formal activities as imposed Islamic boarding schools environment. Thus, it instills the values of religious moderation. This research investigates how the behavior of prophetic leadership instills the values of religious moderation in both Islamic boarding schools. The method used in this research was field research with a qualitative approach designed. It was through a multi-site study with interactive analysis. Therefore, the data obtained was comprehensive. This research found that both Islamic boarding schools view that prophetic behavior leadership was based on the values of faith and piety in every activity, and wise in making decisions, oriented to the interests of the community without gaps, courage in change, responsible to the task, put forward morality, diversity of ideas, being humanist, tolerant instead of different religious status and establishing ukhuwah Islamiyah. Those attitudes are always instilled in the students and the Islamic boarding school community. Artikel ini menjelaskankan tentang kepemimpinan profetik dalam menanamkan nilai-nilai moderasi di lembaga pendidikan Islam. Kepemimpinan profetik yang dijalankan baik di Pesantren Tebuireng maupun Mambaul Ma’arif Denanyar, mencerminkan berbagai pemahaman dan kegiatan dalam kesaharian baik melalui kegiatan formal di lembaga pendidikan maupun non formal lingkungan pesantren sehingga dapat menanamkan nilai-nilai moderasi beragama. Adapun rumusan dalam penelitian ini adalah bagaimana perilaku kepemimpinan profetik dalam menanamkan nilai-nilain moderasi beragama pada kedua pondok pesantren. Metode yang digunakan dalam penelitian ini adalah field reserch dengan pendekatan kualitatif yang dirancang melalui studi multisitus dengan analisis interaktif sehingga data yang diperoleh sangat luas. Hasil penelitinan di kedua pesantren sama-sama berpandangan bahwa perilaku kepemimpinan profetik yang dijalankan berlandaskan nilai iman dan taqwa dalam setiap aktivitas, arif dan bijaksana dalam mengambil keputusan, brorientasi pada kepentingan masyarakat tanpa kesenjangan, keberanian dalam perubahan, amanah atas tugas, mengedepankan akhlaqul karimah, keberagaman ide, bersikap peduli humanis, toleran tanpa status keagamaan dan menjalin ukhuwah Islamiyah sebagai sikap yang selalu ditanamkan kepada para santri dan masyarakat pesantren.